THE MAKING OF LIQUID ORGANIC FERTILIZER FROM GINGER WASTE BY HIGH SCHOOL STUDENTS AT AL HIDAYAH DLANGGU MOJOKERTO - Yusuf, Ah; Rizki Fitryasari; Kotijah, Siti; Manalu, Novita Verayanti; Nayluzzuharo', Fanny; Verantika Setya Putri; Sumiatin, Titik; Surya, Ronal (Jurnal Pengabdian Masyarakat Dalam Kesehatan, 2024)
Introduction: After the production of "Hidayah" ginger drinks, there has been a significant accumulation of ginger waste around AL Hidayah High School. This waste has led to unpleasant odors, attracting flies and creating an unsightly environment. This community service program aims to repurpose ginger waste into something beneficial, such as liquid organic fertilizer. Methods: The community service project employed an educational approach followed by practical sessions in producing organic liquid fertilizer through a biorefinery system. All students at AL Hidayah High School in Dlanggu Mojokerto were involved in this activity, which took place on May 25, 2023. Results: The outcome of this initiative was the production of organic liquid fertilizer using biorefinery methods. Conclusion: The liquid organic fertilizer derived from ginger waste through biorefinery methods has the potential to mitigate several associated issues. It proves to be advantageous for the local community, serving as a plant nutrient and potentially contributing to the school's economic growth if produced in sufficient quantities for market distribution. Furthermore, this endeavor nurtured creativity and entrepreneurial skills among the students.